Arabic 1. The Philosphy of Death and Life in the Poetry of Al-Mutanabbi : فلسفة الموت والحیاة فی شعر المتنبي - Saleem, Dr. Mufti Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The article “The Philosphy of Death and Life in the Poetry of Al-Mutanabbi” the poet Abu Tayub Al-Mutanabbi his poetry is exploring after thourghly studies the poetic powers and the rational ideas of this wise poet who managed to bring the language of reason and the language of heart together. When we lackled his rational work, we noticed the initil share of the reform to the classical quesida. He focused more on Philosophical ideas to keep his peers spirit awake especially these living the political decline after the collapse of califot Abbasside in Baghdad throughait his verses one can discover a great master and a great genius. He is an effective poet, a marvelously clevcs and skillful literary artist, who managed to join the antithesis and dexterity together in order to conuinee the reader and keep his spirit always awake.